The Palestinian Authority after Mahmoud Abbas: Anticipation for the Future - Abujaber, Iyad S. S. (Journal of Al-Tamaddun, 2022)
The article discusses the possible scenarios in the event that the position of the President of the Palestinian Authority (PA) becomes vacant, in light of the absence of an institutional structure of the PA, legal justifications or political solutions that can be relied on, if Palestinian parties choose to resort to the democratic path, to elect a new president, or even bring a successor to the President of the PA, who enjoys popular and regional acceptance. Due to the difficulty of predicting the post-Mahmoud Abbas era, and the absence of any signs or indicators to anticipate the next stage and considering the persistence of the internal Palestinian division including that of the Fatah movement, and the emergence of new political currents, the author applies the scenario approach by presenting a set of possible scenarios, based on the available data and information discussed in some detail in the article. The article presents a theoretical and descriptive reading of the developments of the history of the PA, focusing on legal mechanisms through which the president of the PA is chosen, analyzing, and linking these mechanisms to the current reality of the PA through discussing the most important challenges facing the succession of Abbas. This is done based on the severe divisions within the Fatah movement, and its declining popularity, as well as the influence of regional and international parties. The article relies on many Arab, English, and Hebrew academic sources. It also includes interviews with a group of experts and specialists in Palestinian affairs. With the analysis of each possible scenario for the future of the PA after Abbas, the author concludes that the fourth scenario is most possible and realistic one, which suggests that Palestinians will be able to reach a consensus on a person to lead the PA after Abbas, especially since the absence of consensus could lead to more disintegration and internal fighting.